Inferiority or Even Superiority of Virtual Reality Exposure Therapy in Phobias?—A Systematic Review and Quantitative Meta-Analysis on Randomized Controlled Trials Specifically Comparing the Efficacy of Virtual Reality Exposure to Gold Standard in vivo Exposure in Agoraphobia, Specific Phobia, and Social Phobia - Wechsler, Theresa F.; Kümpers, Franziska; Mühlberger, Andreas (Frontiers in Psychology, 2019)
Background: Convincing evidence on Virtual Reality (VR) exposure for phobic anxiety disorders has been reported. However, the benchmark for phobia treatment is in vivo exposure as gold standard. For direct treatment comparisons, the control of confounding variables is essential. Therefore, the comparison of VR and in vivo exposure in studies applying an equivalent amount of exposure in both treatments is necessary. Methods: We conducted a systematic search of reports published until June 2019. Inclusion criteria covered diagnosis of Specific Phobia, Social Phobia, or Agoraphobia, and a randomized-controlled design with an equivalent amount of exposure in VR and in vivo. We qualitatively reviewed participants’ characteristics, materials, and treatment procedures of all included studies. For quantitative synthesis, we calculated Hedges’ g effect sizes for treatment effects of VR exposure, in vivo exposure, and the comparison of VR to in vivo exposure over all studies and separately for studies on each diagnosis. Results: Nine studies (n = 371) were included, four on Specific Phobia, three on Social Phobia, and two on Agoraphobia. VR and in vivo exposure both showed large, significant effect sizes. The comparison of VR to in vivo exposure revealed a small, but non-significant effect size favoring in vivo (g = –0.20). Specifically, effect sizes for Specific Phobia (g = –0.15) and Agoraphobia (g = –0.01) were non-significant, only for Social Phobia we found a significant effect size favoring in vivo (g = –0.50). Except for Agoraphobia, effect sizes varied across studies from favoring VR to favoring in vivo exposure. Conclusions: We found no evidence, that VR exposure is significantly less efficacious than in vivo exposure in Specific Phobia and Agoraphobia. The wide range of study specific effect sizes especially in Social Phobia indicates a high potential of VR, but also a need for a deeper investigation and empirical examination of relevant working mechanisms. In Social Phobia, a combination of VR exposure with cognitive interventions and the realization of virtual social interactions targeting central fears might have advantages. Considering the advantages of VR exposure, its dissemination should be emphasized. Improvements in technology and procedures might even yield superior effects in future.